2016
DOI: 10.3390/ijms17020146
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents Renal Fibrosis in Mice with Unilateral Ureteral Obstruction and Inhibits Ang II-Induced ECM Production in Renal Fibroblasts

Abstract: Renal fibrosis is the final common pathway of chronic kidney disease (CKD), and no effective medication is available clinically for managing its progression. Metformin was initially developed as an anti-diabetic drug and recently gained attention for its potential in the treatment of other diseases. In this study, we investigated its effects on renal fibrosis in a mouse model of unilateral ureteral obstruction (UUO) in vivo and in angiotensin II (Ang II)–treated renal fibroblast NRK-49F cells in vitro. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 29 publications
4
32
0
1
Order By: Relevance
“…The confidence intervals were wide, and this finding should be interpreted cautiously. However, in the context of prior studies, the lack of an impact on ESRD incidence suggests that the experimental reductions in renal fibrosis observed with metformin use may not translate into a reduction in progressive GFR loss in diabetes. However, it is possible that the fibrosis present in some enrolled patients with stage G4 CKD was advanced and resistant to anti‐fibrotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The confidence intervals were wide, and this finding should be interpreted cautiously. However, in the context of prior studies, the lack of an impact on ESRD incidence suggests that the experimental reductions in renal fibrosis observed with metformin use may not translate into a reduction in progressive GFR loss in diabetes. However, it is possible that the fibrosis present in some enrolled patients with stage G4 CKD was advanced and resistant to anti‐fibrotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies suggest that metformin may have anti‐fibrotic effects, with the potential for beneficial effects on kidney and cardiovascular disease independent of the direct effect on glycaemic control. However, until recently, metformin was considered unsafe for use in individuals with moderate or severe CKD because of the potential to induce lactic acidosis .…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al reported that pretreatment with metformin prevents renal fibrosis by preventing angiotensin II-induced ERK1/2 activation and ECM overproduction in angiotensin II-treated renal fibroblast NRK-49F cells [87]. Fluorofenidone treatment inhibits the progression of renal interstitial fibrosis by suppressing oxidative stress and ERK1/2 signaling pathways in rat proximal tubular epithelial cells [88].…”
Section: Com/cpbmentioning
confidence: 99%
“…The normal overexpression and pathological accumulation of ECM components, such as fibronectin and collagen I, result in ECM deposition [31], thereby decreasing the glomerular infiltration rate, deteriorating renal function, and eventually leading to renal failure. In our study, we demonstrated that fibronectin and collagen I are significantly decreased by treatment with telocytes at both the protein and gene levels.…”
Section: Discussionmentioning
confidence: 99%